Five-axis Trochoidal Flank Milling of Deep 3D Cavities. (February 2020) - Li, Zhaoyu; Chen, Lufeng; Xu, Ke; Gao, Yongsheng; Tang, Kai
Abstract: Trochoidal milling is widely used in slotting and pocketing operation owing to its unique cyclic pattern that restricts the tool-workpiece engagement and hence reduces the cutting force load and helps heat dissipation. Especially when cutting extremely hard materials such as super titanium alloy, trochoidal tool path has been a good milling strategy for reducing tool wear and restraining heat generation. However, the conventional trochoidal milling is two-dimensional in nature and thus can only apply to 2.5D machining. Aiming at further extending the application of trochoidal milling, in this paper we propose a novel five-axis trochoidal flank milling strategy applicable to machining more complex 3D shaped cavities. Rather than the traditional circular trochoidal pattern, our proposed method can adaptively generate a spatial cubic curve-based cyclic five-axis tool path according to the given complex 3D cavity, and, subject to the given tool-workpiece engagement threshold, the material removal rate is maximized in the process of tool path generation. In addition, we also present a scheme of adjusting the tool orientation at the boundary surfaces of the cavity to mitigate the overcut in case they are non-developable. Both computer simulation and physical cutting experiments are conducted and the preliminary results have given a definitive confirmation on the correctness and effectiveness of the proposed method. Highlights: A polynomial curve based five-axis trochoidal flank milling method is proposed. Medial axis surface is generated to guide the spatial trochoidal path planning. Material removal rate is optimized by adjusting the tool path shape parameters. Simulations and experiments are conducted to verify the proposed method.